Plant resistance to Geminiviruses - Patil, B.L.; Chakraborty, S.; Czosnek, H.; Fiallo-Olive, E.; Gilbertson, R.L.; Legg, James P.; Mansoor, S.; Navas-Castillo, J.; Naqvi, R.Z.; Rahman, S.; Zerbini, F.M. (Elsevier, 2021)
Geminiviruses cause major damage to crop plants and evolve through mutations, recombination and pseudo-recombination, expanding their host range and becoming pandemic due to international trade and invasive vector species. Management of geminiviruses consists of breeding resistant crops by employing natural resistance genes from different cultivated or related wild plant species. Compared to other plant viruses, such as potyviruses, the information on resistance genes/loci identified for geminiviruses is scarce. Other strategies have been developed based on the virus genome; however, these have not yet reached the commercial field. Here we catalog and describe the resistance genes/loci identified against the most important geminiviruses, in the most economically important crops they infect: cassava, tomato, bean, maize and cotton.